Prosecuting war criminals: an analysis into international humanitarian law / Adilah Ruqaiyah Ahmad Nasir and Sania Nasim Hamayon - Ahmad Nasir, Adilah Ruqaiyah; Hamayon, Sania Nasim (2008)
This research analyses the reasons for failed prosecutions of war crimes with regards to international humanitarian law. The first chapter goes into the essence and structure of the research, and all the necessary conceptual features are introduced to ensure readers' understanding. The second chapter goes into the structure of the system of modern war crimes prosecutions, where the researchers also introduced the institutions responsible for prosecuting war crimes. The third chapter goes into a description of modern war crimes prosecution, where the researchers made mention of flaws surrounding the trials. The fourth chapter then focused on an analysis of the inherent problems preventing successful prosecutions of war crimes perpetrators. Our research concludes with a consideration of whether the current system is a flawed but workable system or should be done away with altogether, and has made several recommendations to improve the current system.